THEORETICAL JUSTIFICATION AND FIELD RESEARCH ON CONSTRUCTIVE SCHEME OF A NEW TOP HARVESTER - Адамчук, В. В.; Булгаков, В. М.; Головач, І. В.; Борис, М. М.; Ігнатьєв, Є. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Digital calculation of sugar-bearing mass losses and remnants of tops at sugar beet crowns on the basis of mathematical modeling of non-sensing topping was carried out. The results of calculation of non-sensing topping are represented in dependency diagrams. Dependency diagram display a graphical view of relationships between sugar-bearing mass losses, remnants of tops and the parameters of normal distribution of sugar beet crown height over soil surface and cutting height according to soil surface. The study demonstrates that it is impossible to get the quality of beet tops harvesting with the help of non-sensing cut provided that the agro technical requirements are met. The author suggests a new technological scheme for a two-stage top separation. The first stage concerns non-sensing of high level sugar beet crowns. And the second stage is after-cleaning of beet roots. The results of field experimental studies on top harvester were developed according to new technological scheme. It can be concluded that optimal operation mode for such type of car is the travelling speed of about 2.0 m∙s-1